Relationship between Increased Sitting Time and Neck, Back and Shoulder Arch Pain During the Covid-19 Quarantine - Vygantas Stikleris; Vilma Dudonienė (Lithuanian Sports University, 2022)
Background. Coronavirus disease (Covid-19) originating in Wuhan, China in December 2019 spread worldwide rapidly. To avoid direct contact, quarantine was implemented globally, which changed employees' work habits, leading to longer sedentary times and increased complaints of neck, back and shoulder arch pain. Aim. To analyse the association of increased sitting time during quarantine with neck, back and shoulder arch pain. Methods. The survey involved 180 respondents, 136 women (76.0%) and 43 men (24.0%), who participated in a questionnaire survey conducted in social networks. The questionnaire consisted of closed-ended questions. Statistical analysis was performed using the Spearman correlation coefficient to determine the relationship between sitting time and neck, back, and shoulder arch pain. Results. It was found that the time spent at the computer or TV screen during the quarantine and before quarantine differed statistically significantly (p <0.005). Respondents (40.8%) indicated that they spent 1-2 hours in front of the TV or computer screen, before the quarantine, and during the quarantine most respondents (57.0%) stated that they spent more than 5 hours. More than half of the respondents (56.4%) said that their well-being had recently deteriorated. Prolonged sitting time was mentioned by the majority of respondents (63.2%) as the main cause of deteriorating health. Respondents rated their pain before quarantine at 3.25 ± 1.92 points and during quarantine at 5.84 ± 2.12 points. Conclusions. Respondents' time spent at the computer or TV screens more than doubled during the pandemic, with the vast majority complaining of back, neck and shoulder pain. There was a direct relationship between back, shoulder arch and neck pain and sitting time. Keywords: pain, sitting time, quarantine, lack of physical activity.